A short cut to definitive airway in open tracheal injury: a case report - Saifful NI,; Afliza Abu Bakar,; Tan, TL (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Open tracheal injury is rare but can lead to disastrous consequences such as massive bleeding, airway obstruction or failure and aspiration of blood. We present a case of open tracheal injury of a man who tried to attempt suicide using a knife. In this case, the initial management was securing the airway by attempting orotracheal intubation. However, it was unsuccessful when the tube came out from the laceration wound. Intubation was then re-attempted through the distal cut-end of the trachea in the face of airway failure. A quick initial assessment and anticipation of a failed airway should always be the top priority in any emergency physician managing these cases. Direct intubation through the laceration wound might be the only option when all else fail and your patient is crashing.